2019
DOI: 10.2196/13579
|View full text |Cite
|
Sign up to set email alerts
|

Mobile and Web-Based Apps That Support Self-Management and Transition in Young People With Chronic Illness: Systematic Review

Abstract: BackgroundMore adolescents with chronic physical illness are living into adulthood, and they require the development of proficient self-management skills to maintain optimal physical health as they transition into adult care services. It is often during this vulnerable transition period that deterioration in illness control is seen as a result of inadequate self-management skills and understanding of their chronic illness. Mobile technology has been proposed as an innovative opportunity to assist in improving … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 40 publications
(128 reference statements)
1
41
1
3
Order By: Relevance
“…The use of health technologies by CYP to manage LTCs is increasing with many studies describing their development, acceptability and use by CYP 45 53–61 ; effectiveness 53 62–64 ; and compliance by CYP. 41 57 However, there is limited literature on the concerns that CYP may have when (or before) using a health technology for self-managing their LTC, and no review has specifically explored these concerns.…”
Section: Discussionmentioning
confidence: 99%
“…The use of health technologies by CYP to manage LTCs is increasing with many studies describing their development, acceptability and use by CYP 45 53–61 ; effectiveness 53 62–64 ; and compliance by CYP. 41 57 However, there is limited literature on the concerns that CYP may have when (or before) using a health technology for self-managing their LTC, and no review has specifically explored these concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the potential of the use of technology in increasing adherence outcomes during the transition period, research on its use remains limited [ 50 , 51 ] but is likely to grow given the current rise of telemedicine and telehealth interventions. The few studies that have addressed this topic have yielded mixed findings [ 50 ], and published materials frequently describe the methods rather than yet being able to share actual study results [ 52 55 ].…”
Section: Interventions In Adherencementioning
confidence: 99%
“…The few studies that have addressed this topic have yielded mixed findings [ 50 ], and published materials frequently describe the methods rather than yet being able to share actual study results [ 52 55 ]. Two very recent comprehensive reviews concluded that, although adolescents and young adults were receptive to the technology, efficacy data were lacking [ 51 , 56 ]. Given the potential (although not yet realized) benefit of technological advances, we review some of the relevant studies here.…”
Section: Interventions In Adherencementioning
confidence: 99%
“…They are cost-effective, convenient, easily accessible, personalizable, and can be operated without professional health care assistance [ 26 , 27 ]. mHealth-based approaches have become very popular in chronic health care management and include, among other things, automated text reminders, frequent and accurate symptom monitoring, daily reminders for medication use, follow-up of food intake, education, tips, support, and condition tracking [ 25 , 28 , 29 ]. As such, technological interventions have the potential to contribute to managing gastrointestinal health conditions such as CD [ 30 ].…”
Section: Introductionmentioning
confidence: 99%